Avaliação do teste de Elisa indireto para o diagnóstico de mormo - Takeuti, Rafael Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Glanders is a reemerging infectious-contagious disease caused by the Burkholderia mallei bacterium, which affects equidae, which can affect humans and other carnivorous animals and small ruminants; Therefore, presents a great risk to the health of animals and humans according to the World Organization of Animal Health (OIE), in Brazil the mormo is obligatory notification and actions are coordinated by the Ministry of Agriculture, Livestock and Supply (MAPA), Through the National Equine Health Program (PNSE), established by normative instruction nº 17, of May 8, 2008. The objective of the study was to analyze the use of the indirect ELISA test in the diagnosis of glanders. For that, five studies were obtained that fit the proposed criteria, being one of Google academic in Portuguese and four of PubMed in English. In this present study, it was possible to conclude that the indirect ELISA test is efficient with a promising future for serological diagnosis of glanders, since it presents better sensitivity and specificity
Keywords: Cavalo; Doenças transmissiveis; Equino; Mormo; Glanders